The Studio Jazz Ensemble; Studio Jazz Ensemble II; Vocal Jazz Ensemble, March 10, 1986 - (:unkn) unknown (My University, 1986)
Concert program for The Studio Jazz Ensemble; Studio Jazz Ensemble II; Vocal Jazz Ensemble, March 10, 1986